ORC units driven by engine waste heat – a simulation study. (December 2017) - Luo, Liqi; Wang, Yaodong; Chen, Haisheng; Zhang, Xinjing; Roskilly, Tony
Abstract: ORC (organic Rankine cycle) technology is promising in industry for utilizing low-grade heat to generate electricity. It is acknowledged that in an internal combustion engine, only a small amount of primary fuel energy can be effectively used for the power generation, and the other part of the energy lost through exhaust gas, cooling of elements and overcoming friction. The heat in exhaust gas and cooling system (jacket water) can be used as a heat source to drive ORC units for power generation. In this way, the energy lost can be recovered to generate extra power. In this study, Ricardo Wave software was used to investigate the amount of waste heat available from a 1-cylinder diesel engine and THERMOLIB toolbox in SIMULINK was used to simulate and evaluate the performance of a small ORC unit designed for the application. The simulation results from the engine and ORC models were validated against experimental data from other researchers. Two different heating methods to the ORC were used: a) directly driven by the exhaust gas and jacket water (EG-JW); b) thermal oil (TO) was used to collect the waste heat from the engine exhaust gas; the heated thermal oil together with jacket water were then used to drive the ORC. It was found that the performance of the ORC was improved and it was more stable when using TO under different engine running conditions than that directly driven by EG-JW.